ANALISIS YURIDIS TERHADAP WEWENANG OTORITAS JASA KEUANGAN DALAM MENGAWASI TINGKAT KESEHATAN BANK - Widodo Ramadhana; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2018)
ABSTRACT The Financial Services Authority is expected to minimize the risks that may arise through regulating and overseeing activities in the banking sector, at least reminding the need for careful risk handling, even if it is necessary to prohibit banks from engaging in certain activities that tend to invite high risk to bank health the crisis on the financial system and banks is expected to detect early on the root of bank problems in assessing the soundness of banks, so as to better reflect the condition of the bank. The formulation of the problem in the thesis research is how the authority of the Financial Services Authority in granting licenses for the establishment of the bank. How is the institutional relationship between the Financial Services Authority and Bank Indonesia related to the Bank's soundness. How is the authority of the Financial Services Authority in overseeing the Bank Soundness.The type of research used is normative law and the nature of the research is descriptive. Data used are primary and secondary data, consisting of primary, secondary, and tertiary legal materials. Techniques and data collection tools were conducted by library study and field study by conducting interviews. Data analysis was done by qualitative analysis method.Under Article 7 of the Financial Services Authority Act, the Financial Services Authority declares that the Financial Services Authority has the authority to regulate and supervise the Bank's institutions which include licensing for establishment of a bank. In this Coordination Protocol as a forum for reconciliation between the Ministry of Finance, Bank Indonesia, the Financial Services Authority and the Deposit Insurance Corporation in a coordination forum called the Financial System Stability Committee (KSSK). Coordination in this committee is made if it is not possible to handle banking problems by the Financial Services Authority in relation to the settlement and handling of a failed bank that is suspected to have a systemic impact. The Financial Services Authority also requires the controlling shareholders or investors to increase the capital of the Systemic Bank and be able to convert the type of debt or investment to increase the capital of the systemic bank if faced with potential crisis. Keywords: Authority, Financial Services Authority, Supervision, Bank Health Level.